The emergence of conventional theater and its implications for the theatrical scenery (scenic design – the structure of the play and mise-en-scène – costume design) - Hamza, Moayyad (Имагология и компаративистика)
Vsevolod Meyerhold was one of the most influential theorists of conventional theater who actively promoted creative models he laid out in his articles, speeches, and lectures. This study analyzes Meyerhold’s perspective of conventional theater, drawing on the available modern sources. In relation to Meyerhold and other pioneers of this theatrical approach, the article aims to clarify the concept of conventional theater in terms of scenery. The author focuses on the specificity of theatrical conventions and the origins of Meyer-hold’s artistic creativity in his theorizing about the politics of theater, which depends on the use of the viewer’s imagination and their involvement in the theatrical play.